2018
DOI: 10.1371/journal.pone.0195844
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor suppresses proliferation and metastasis in renal cell carcinoma cell lines via regulating the expression of the epithelial Ca2+ channel TRPV5

Abstract: We previously demonstrated that transient receptor potential vanilloid subfamily 5 (TRPV5) expression was decreased in renal cell carcinoma (RCC) compared with that in normal kidney tissues, a finding that was correlated with vitamin D receptor (VDR) expression, but further investigations is warranted. The aim of this study was to elucidate whether VDR could regulate the expression of TRPV5 and affect proliferation and metastasis in RCC. In this study, we used lentivirus to conduct the model of VDR overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
(37 reference statements)
1
21
0
1
Order By: Relevance
“…VDR is one of the most studied tumor suppressor genes and acts as a transcription factor and regulates numerous physiologic processes, such as serum calcium regulation, cell proliferation and differentiation, and immunomodulatory functions 3 . We previously demonstrated that VDR overexpression signi cantly suppresses RCC cell proliferation, migration and invasion 11 . VDR could inactivate mutations, deletions, and promoter methylation to regulate cell proliferation and differentiation 4,28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VDR is one of the most studied tumor suppressor genes and acts as a transcription factor and regulates numerous physiologic processes, such as serum calcium regulation, cell proliferation and differentiation, and immunomodulatory functions 3 . We previously demonstrated that VDR overexpression signi cantly suppresses RCC cell proliferation, migration and invasion 11 . VDR could inactivate mutations, deletions, and promoter methylation to regulate cell proliferation and differentiation 4,28 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, VDR expression was signi cantly reduced in RCC compared to normal kidney tissue and was associated with RCC prognosis [7][8][9][10] . Speci cally, our previous studies showed that VDR overexpression could signi cantly inhibit RCC cell proliferation, migration, and invasion, and promote apoptosis and con rmed that VDR expression was associated with RCC pathological types 10,11 . These results indicate that VDR may play a key role in RCC development and progression.…”
Section: Introductionmentioning
confidence: 90%
“…It is worth mentioning that calcitriol (100 nM) also up-regulates the expression of TRPV6 in T47D breast cancer cells (Bolanz et al, 2008). Recently, Chen et al (2018) showed that the expression of the calcium channel TRPV5 inversely correlates with the expression of the VDR in renal cancer cells. Knockdown of TRPV5 in these cells inhibited cell proliferation, migration, and invasion induced by VDR knockdown.…”
Section: Regulation Of Ion Channels By Vitamin D and Calcitriolmentioning
confidence: 99%
“…Dentre a variedade de funções e participação da VD em diferentes processos biológicos podemos citar a homeostase óssea e absorção de cálcio pelo intestino(Veldurthy et al 2016), propriedade imunomoduladora (Hardiman et al, 2016) e anti-inflamatória(Mousa et al 2018). Além disso, há evidências que a VD também regula processos de apoptose(Pan et al 2010) em células tumorais bem como a modulação da angiogênese(Bao et al 2006), proliferação, invasão e metástase tumoral(Chen et al 2018).…”
unclassified